Post a New Question

Math

posted by on .

I am trying to find the standard form of this equation for an ellipse.

9x^2 + 4y^2 - 36x + 8y + 31 = 0

First I grouped the x and y's together.

9x^2 - 36x + ? + 4y^2 + 8y + ? = -31 + ? + ?

Then I factored the 9 and 4.

9(x^2-4x+4) + 4(x^2+2x+1) = -31+36+4

9(x-2)^2 + 4(x-1)^2 = 9

Then I divided it all by 9 and got:

(x-2)^2 / 1 + 4(x-1)^2 / 9 = 1

Is this correct or did I mess up somewhere?

  • Math - ,

    looks good

    other than, you lost the y's, but I think that is just a typo.

  • Math - ,

    you're wrong

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question